Symposium 6: Participatory design in PALETTE project : Building a collective methodological approach - Charlier, Bernadette; Daele , Amaury; Esnault, Lilliane; Henri, France; Saunders, Murray (Proceedings of the International Conference on Networked Learning, 2008)
The objective of this paper is to report on the preliminary results concerning the building of the participatory design methodology which is being developed using a participatory approach and supported by the implementation of participatory management in the context of the European project PALETTE. PALETTE integrates computer scientists, educational scientists and members of Communities of Practice with the objective to improve and facilitate the living and functioning of CoPs by developing integrated technological services as well as online learning services. The paper builds upon key elements which were crucial for implementing Participatory Design in PALETTE.